Efektivitas Format Iklan Komparatif dan Non Komparatif Merek Market Leader - Krisna Adryanto; Tandiyo Pradekso; Djoko Setiabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2013)
Jurnal Interaksi (Edisi Oktober, 2013)Page 2Efektivitas Format Iklan Komparatif dan Non KomparatifMerek Market LeaderKrisna Adriyanto, Tandiyo Pradekso1, dan Djoko Setyabudi2ABSTRACTField Experimental Research, 2 (Ad Formats) X 2 (The Difference between Men andWomen in Information-Proccessing Strategies) Randomized-Blocked Factorial Designwas conducted involving 120 participants (60 men and 60 women), who were assignedinto 4 (four) treatment groups. Stimulus used in this research are non-comparative andindirect comparative ads which used by the brand